Acute Otitis Media Severity: Association with Cytokine Gene polymorphisms and other Risk Factors - McCormick, David P. (2011)
BACKGROUND: We have previously shown an association between polymorphisms of proinflammatory cytokine genes and susceptibility to upper respiratory tract infection and acute otitis media. It has not been known whether polymorphisms or risk factors are associated with the severity of acute otitis media. OBJECTIVE: To evaluate the influences of proinflammatory cytokine gene polymorphisms and other risk factors on severity of acute otitis media following upper respiratory infection. METHODS: In a prospective, longitudinal study, children aged 6-35 months were followed for one year for occurrences of upper respiratory tract infection and acute otitis media. Children were studied for TNFα(-308), interleukin (IL)- 6(-174) and IL-1 ß(+3953) polymorphisms, taking into account age, gender, race, family history of otitis, tobacco smoke exposure, breast feeding, day of upper respiratory tract infection at the time of diagnosis and pneumococcal vaccine status. Symptoms and signs of acute otitis media were graded according to a validated scale. The association between acute otitis media clinical severity, polymorphic genotypes, and risk factors was analyzed using statistical models that account for multiple episodes of acute otitis media per child. RESULTS: A total of 295 episodes of acute otitis media in 128 subjects were included. More severe acute otitis media symptoms were associated with young age (P=0.01), family history of acute otitis media (P=0.002), tobacco smoke exposure (P=0.008), and early diagnosis of otitis after onset of upper respiratory tract infection (P=0.02). Among children with a bulging or perforated tympanic membrane (206 episodes, 104 subjects), those who had the IL- 1 ß(+3953) polymorphism, experienced higher symptom scores (P<0.02). CONCLUSION: This is the first report of the association between risk factors and acute otitis media severity. Risk factors such as tobacco smoke exposure and a positive family history appear to be more significantly associated with acute otitis media severity than proinflammatory gene polymorphisms. Clinical severity may be an important factor contributing to the incidence and costs of acute otitis media, because children with more severe symptoms might be more likely to be brought for a medical visit, receive a diagnosis of acute otitis media, and be prescribed an antibiotic.